Circulation, hydrography, and transport over the summit of Axial Seamount, a deep volcano in the Northeast Pacific. Issue 7 (7th July 2017) - Xu, G.; Lavelle, J. W.
Abstract: A numerical model of ocean flow, hydrography, and transport is used to extrapolate observations of currents and hydrography and infer patterns of material flux in the deep ocean around Axial Seamount, a destination node of NSF's Ocean Observatories Initiative's Cabled Array. Using an inverse method, the model is made to approximate measured deep ocean flow around this site during a 35 day time period in the year 2002. The model is then used to extract month‐long mean patterns and examine smaller‐scale spatial and temporal variability around Axial. Like prior observations, model month‐long mean currents flow anticyclonically around the seamount's summit in toroidal form with maximum speeds at 1500 m depth of 10–11 cm/s. As a time mean, the temperature (salinity) anomaly distribution takes the form of a cold (briny) dome above the summit. Passive tracer material continually released at the location of the ASHES vent field exits the caldera primarily through its southern open end before filling the caldera. Once outside the caldera, the tracer circles the summit in clockwise fashion, fractionally reentering the caldera over lower walls at its north end, while gradually bleeding southwestward during the modeled time period into the ambient ocean. A second tracer release experiment using a source of only 2 day duration inside and near the CASM vent field at the northern end of the caldera suggests a residence time of the fluid at that locale of 8–9 days. Key Points: Anticyclonic toroidal mean and barotropic/internal tidal currents dominate motion at the summit of Axial Time‐averaged temperature and salinity show lateral gradients within the caldera while their anomalies dome above the seamount Passive tracers originating inside the caldera are trapped to Axial before eventually bleeding off into the distal ocean